Qualidade de meis de abelhas Apis mellifera comercializado no Estado de Alagoas - Alves, Thaís Patrícia (2013)
This study aimed at evaluating the quality of honey sold in the State of Alagoas, Brazil. 15 honey samples of Apis mellífera L. were acquired from street market and cooperatives, all located in the State Alagoas. The caracteristicas physico-chemicals and microbiological were evaluted, in order to verify a possible adulteration and setting a microbiological standard for honey investigated. The physico-chemical analisys showed that all the samples studied presented pH values acid racing between 2,3 and 4,4, for enzymatic activity, ligol reaction that are indicatives the presence of starch and dextrina and the Fiehe reaction, that a qualitative indicator of HMF, all the samples showed unsatisfactory result in at least of the parametres. As for microbiological standard, 26,6%, of the total of the samples showed high counts mesophilic aerobic bacteria standard, 20% showed counts of yeasts and moulds above the quality standards established by Brazilian law. in relation to enumeration coliform 35º and 45º, showed that the most samples were highly contaminated (86,7). The results showed that 13,3% samples were positive to the presence of clostridium botulinum, identified by smear slide and stained by the Gram method, both under aerobic condictions as anaerobic conditions. According to the results presented, there necessity the implantation of quality control programs production chain and processed of honey, as effective supervision and the development of the new standards for microbiological analisys for honey, aimed to ensure the consumers' health.